Surviving in cities: the case of a year-round territorial bird in the Neotropics. Issue 1 (18th March 2022) - Juárez, Roselvy; Ruiz-Gutiérrez, Viviana; Sandoval, Luis
Abstract: Urban expansion has been identified as one of the main threats to biodiversity because it can negatively affect wildlife populations. However, wildlife population dynamics have not been studied in one of the most rapidly urbanizing regions in the world—the Neotropics. To examine the effect of urbanization on the population dynamics of Neotropical wildlife, we used recapture data from a marked population (2011–2017) of White-eared Ground-Sparrow ( Melozone leucotis ) across an urban–rural gradient in the Costa Rican Central Valley. Additionally, we tested if this effect differed between males and females. Contrary to our prediction, ground-sparrow survival rates were higher in urban and suburban sites than in the rural site, and we found that survival was positively correlated to the proportion of urban surface inside each territory (β = 0.90, 95% CI: 0.71–0.97). We did not find differences in survival rates between the sexes and the mean survival rate was high overall (0.79 ± 0.06). Surprisingly, our results suggest that the survival rate of this urban avoider is positively influenced by urbanization, and therefore, suggest that the potential cost to some urban avoiders may not be driven by reduced survival in more urbanized environments, and could be driven by reductions in other vital rates. Therefore, we encourage research to evaluate multiple vital rates of urban avoiders and urban adapters to achieve more comprehensive knowledge on how urbanization is affecting avian populations in the Neotropics.